Peran Kepala Sekolah dalam Menanamkan Budaya Mutu Pendidikan di SMKN 3 Rejang Lebong - Ade Wahyu Kurniawan; Fakhruddin Fakhruddin; Abdul Sahib (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to determine the role of the principal in instilling a culture of quality education in schools. This qualitative descriptive research method takes the background of the State Vocational High School 3 Rejang Lebong. Methods for collecting data were direct interviews, observation, and documentation. The subjects of this research were the Principal of SMKN 3, Rejang Lebong, and the Deputy Head of Quality Assurance. The research object was carried out at SMKN 3 Reajang Lebong. Qualitative data is analyzed by identifying, clarifying, analyzing, and concluding data. The results of the research show: the role of the principal in instilling a culture of quality school education at SMKN 3 Rejang Lebong, which in the learning curriculum is used as a guideline for implementing learning activities with the aim of achieving education where the learning process emphasizes character formation, namely Active, Creative, Enthusiastic, Clean and Religious (AKBAR), as well as learning about the environment both internally and externally which will later be formulated to solve problems that arise in the school environment in order to realize the quality of education at SMKN 3 Rejang Lebong; The school principal carries out a strategy to achieve an effective school, namely through learning carried out optimally, students' potential is empowered as best as possible by aligning the curriculum with the business world and the industrial world in accordance with each skill competency at SMKN 3 Rejang Lebong, where currently SMKN 3 Rejang Lebong has collaborated with more than 65 industrial worlds, business worlds and MSMEs, as well as other agencies such as Bataliyon 144 Jaya Yuda and Kodim 0409 RL in the Latdastar Program; Obstacles or problems for a school principal in implementing a culture of quality education at SMKN 3 Rejang Lebong include limited facilities and infrastructure that do not support this due to the little land owned by SMKN 3 Rejang Lebong, as well as the diversity of ethnic cultures of its students. In conclusion, the principal has a role in instilling a culture of quality school education, which is included in the learning curriculum and is a reference in carrying out the learning process. Keywords: Role of the Principal, Educational Quality Culture